63.3k views
5 votes
For f(x) =4x+1 g(x)=x²-5, find (f•g)(x)​

2 Answers

3 votes

Given :


  • \sf f(x) =4x+1

  • \sf g(x)=x²-5

To Find :


  • \sf (f . g)(x)

Solution :

We know that,


\Large \underline{\boxed{\sf{ (f . g)(x) = f(x) * g(x) }}}

By substituting values :


\sf : \implies (f . g)(x) = (4x+1) * (x^(2) -5)


\sf : \implies (f . g)(x) = 4x(x^(2) -5) +1(x^(2) -5)


\sf : \implies (f . g)(x) = 4x^(3) - 20x + x^(2) -5


\sf : \implies (f . g)(x) = 4x^(3) + x^(2) - 20x -5

Hence, answer is :


\underline{\boxed{\sf{(f . g)(x) = 4x^(3) + x^(2) - 20x - 5}}}

User David Glickman
by
4.4k points
4 votes

Answer:

(f · g)(x) = 4x³ + x² - 20x - 5

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Combining Like Terms
  • Expand by FOIL (First Outside Inside Last)

Explanation:

Step 1: Define

f(x) = 4x + 1

g(x) = x² - 5

(f · g)(x) is f(x)g(x)

Step 2: Find (f · g)(x)

  1. Substitute: (f · g)(x) = (4x + 1)(x² - 5)
  2. Expand [FOIL]: (f · g)(x) = 4x³ - 20x + x² - 5
  3. Combine like terms: (f · g)(x) = 4x³ + x² - 20x - 5
User Hasan Hafiz Pasha
by
4.5k points